2020
DOI: 10.3390/molecules25143130
|View full text |Cite
|
Sign up to set email alerts
|

RNA Granules: A View from the RNA Perspective

Abstract: RNA granules are ubiquitous. Composed of RNA-binding proteins and RNAs, they provide functional compartmentalization within cells. They are inextricably linked with RNA biology and as such are often referred to as the hubs for post-transcriptional regulation. Much of the attention has been given to the proteins that form these condensates and thus many fundamental questions about the biology of RNA granules remain poorly understood: How and which RNAs enrich in RNA granules, how are transcripts regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 157 publications
3
54
2
Order By: Relevance
“…We show that in vivo CP-puncta only form in bacterial cell poles. The puncta survive cell lysis, and in vitro a mix of the same RNA and proteins form similar puncta that are consistent with current understanding of RNP granule formation and phase transition models (Tian et al, 2020). By tracking puncta fluorescent signals in vivo , we demonstrate that for all slncRNA molecules used in our experiment, the various puncta emitted similar signals characterized by bursts of increasing or decreasing fluorescent intensity.…”
Section: Introductionsupporting
confidence: 81%
“…We show that in vivo CP-puncta only form in bacterial cell poles. The puncta survive cell lysis, and in vitro a mix of the same RNA and proteins form similar puncta that are consistent with current understanding of RNP granule formation and phase transition models (Tian et al, 2020). By tracking puncta fluorescent signals in vivo , we demonstrate that for all slncRNA molecules used in our experiment, the various puncta emitted similar signals characterized by bursts of increasing or decreasing fluorescent intensity.…”
Section: Introductionsupporting
confidence: 81%
“…Condensates at cell membranes ( 81 ) and in the cytosol have been shown to regulate cell division, migration and invasion ( 82 , 83 ), transgenerational memory ( 84 , 85 , 86 ), and immunomodulation ( 87 ) in response to a variety of morphogens and endo/para/autocrine signals. In addition to acting across a range of timescales, condensation in response to external perturbations plays a critical role in shaping the spatial organization of cells by moving RNAs and proteins into dynamic MLOs with complex organization, suggesting an intimate relationship between macromolecular sequence, intracellular organization, and the extracellular environment ( 66 , 88 , 89 , 90 ).…”
Section: Phase Separation In Response To Environmental Fluctuationsmentioning
confidence: 99%
“…RBPs are of great importance in RNA–protein interactions, which are characterized by the recognition of a specific sequence or structural element in the target RNA by an RNA-binding domain (RBD) such as an RRM or K homology domain [ 139 ]. In addition, RBPs appear frequently in LLPS [ 140 ]; the sequence-binding specificity of different RBDs may determine the processing of a certain subset of nascent RNAs in a particular droplet. High-throughput studies have shown that the RNA-binding proteomes of plants can be divided into three categories: RBPs containing classical RBDs (22%), RBPs containing non-classical RBDs (39%), and RBPs containing unknown RBDs (39%) [ 141 ].…”
Section: Discussionmentioning
confidence: 99%